Cardiac Manifestations in Dengue Patients in a Rural Tertiary Care Centre in Coastal Kerala - Poornima, H.; John, Juby (International Journal of Innovative Research in Medical Science, 2019)
Background: Dengue epidemic is a major health problem in India. Kerala has reported the highest number of dengue related deaths in the country in 2017 as per the reports of the directorate of National Vector Borne Disease Control Programme (NVBDCP). The aim of the present study is to find out the cardiac manifestations of patients admitted with dengue fever during the epidemic in 2017 in a rural tertiary care centre in coastal Kerala. Method: 341 patients who were admitted in the medicine department of a rural tertiary care Centre in Kerala with Dengue were included in the study. W.H.O case definitions were used for the diagnosis. Complete blood counts, RBS, serum creatinine and liver function tests and E.C.G were carried out in all patients. Echocardiogram and cardiac biomarkers were done when indicated. Results: Males predominated. 317 were diagnosed as dengue fever, 12 as dengue hemorrhagic fever and 12 had dengue shock syndrome. Only four patients succumbed to death. Head ache and myalgia were the common symptoms at the time of presentation. 72 patients had abnormal ECG, but all had normal ECG at the time of discharge, indicating a transient change during the episode. Conclusion: This retrospective observational study included 341 patients admitted in a rural tertiary care Centre in Kerala. Patients were diagnosed as per W.H.O. case definition for dengue. 317 were diagnosed as dengue fever, 12 as dengue hemorrhagic fever and 12 had dengue shock syndrome. Study population was predominantly males. 72 patients had abnormal ECG, but all had normal ECG at the time of discharge, indicating a transient change during the episode.